Business Development Training by Taking Pineapple Leaf Fiber in Ngancar Farmers' Group: Pelatihan Pengembangan Usaha dengan Pengambilan Serat Daun Tanaman Nanas Pada Kelompok Tani Ngancar - Habibi, Imam (Jurnal Soeropati, 2022)
Pineapple is an important commodity in Kediri regency, pineapple is very popular because it tastes sweet and has a sour taste, and contains nutrients and antioxidants. The service activity involved the UNISKA faculty of agriculture in collaboration with the pineapple farmer group and PT. PNM Kediri Branch. The objectives of the activity are identification of pineapple farmers' problems through survey activities, solve problems through survey activities, and solve problems through training activities. Pineapple leaf fiber extraction in Kediri regency is not widely known. Farmers still rely on sales in the aspect of pineapple, so it is necessary to add value to the product. The training was carried out in November 2019. The tools and materials used were a 200 liter tank, decomposing microbes, and water. The output of activity is a cluster map of pineapple farmers in Kediri regency and product diversification from pineapple plants. The results obtained are that farmers can produce fiber from pineapple leaves and business assistance for pineapple plants.